Fusobacterium nucleatum induces MDSCs enrichment via activation the NLRP3 inflammosome in ESCC cells, leading to cisplatin resistance. (31st December 2022) - Liang, Mengxia; Liu, Yiwen; Zhang, Zheyuan; Yang, Haijun; Dai, Ningtao; Zhang, Ning; Sun, Wei; Guo, Yibo; Kong, Jinyu; Wang, Xiaopeng; Wang, Min; Zhou, Fuyou
Abstract: Background: To analyse the regulatory effect of Fusobacterium nucleatum (Fn) on NOD-like receptor protein 3 (NLRP3) and myeloid-derived suppressor cells (MDSCs) in oesophageal squamous cell carcinoma (ESCC) as well as its effect on cisplatin (CDDP) therapy and to explore its clinical significance. Methods: Fn infection, NLRP3 expression and MDSCs infiltration in ESCC tissues were detected by RNAscope and immunohistochemistry (IHC). The correlation between these three factors and the clinicopathological features and survival of ESCC patients was analysed. A coculture system of human peripheral blood monocytes (PBMCs) and ESCC cells was established to simulate the tumour microenvironment. In vitro and in vivo models were used to analyse the effects of Fn on the percentage of MDSCs in the coculture system and the NLRP3 expression level and CDDP sensitivity of ESCC cells. Results: Fn infection was consistent with high NLRP3 expression and MDSCs enrichment in ESCC tissues. Moreover, the survival time of ESCC patients was significantly shortened under Fn infection, high NLRP3 expression and MDSCs enrichment. In the in vitro and in vivo models, Fn induced abundant enrichment of MDSCs by inducing high expression of NLRP3 in ESCC cells and reducing the sensitivity of ESCC cells to CDDP. Conclusions: Fn infection can induce high expression of NLRP3 in ESCC, lead to MDSCs enrichment, weaken the body's antitumour immunity, and lead to CDDP treatment resistance. The effective elimination of Fn and the inhibition of MDSCs enrichment may provide new strategies and treatments for ESCC. Highlights: The survival of ESCC patients with Fn infection, high NLRP3 expression and MDSCs enrichment was significantly shortened. Fn infection could cause CDDP resistance in ESCC. Fn could induce the enrichment of MDSCs in the tumour microenvironment by activating NLRP3 in ESCC cells.